Nutritional content, digestibility and performance of native grasses biomass that dominate livestock Molinopampa, Pomacochas and Leymebamba basins, Amazonas, Peru - Oliva, Manuel (2015)
The objective of this research was to analyze the nutritional content, in vitro digestibility and performance of biomass and species as farmers are the most important species of native grasses that predominate in the three main livestock basins of the Amazonas: Molinopampa, Pomacochas and Leymebamba. For this random sampling, six areas of 0.25 m2 per treatment every 60 days for three outbreaks. The obtained samples were separately weighed and mixed, and then extract a uniform and representative aliquot of 1 kg per species to be dehydrated in an oven at 60 °C for 48 hours, they were subjected to a proximate analysis. Values obtained with each of the evaluation parameters and after being multiplied with respective values final cumulative weighted value being calculated the following results Trifolium repens L (35.9), often Philoglossa mimuloides-Often Siso (35.3), Cenchrus clandestinus (32.8), Trifolium dubium (32.5) and Philoglossa mimuloides-Siso lapacho (31.3). The values mean the cumulative importance of each species.